26 Day case CRYO-balloon ablation procedures: a single centre experience in trends, safety and cost effective analysis. (June 2018) - Arujuna, Aruna; Velu, Selvakumar; Pathiraja, Janaka; Lapper, Andrew; Kidd, Geoff; Forsey, Peter; Hado, Hussien; Barr, Craig; Arya, Anita; Petkar, Sanjiv
Abstract : Background: Despite the increasing evidence on the efficacy of the second-generation cryoballoon (CB) ablation in patients with atrial fibrillation (AF), data on the utility of CB ablation as a day case procedure is missing. Same day discharge following AF ablation is at present time a guideline free zone. This study analyses the practice in view of safety and cost effectiveness of day case CB (DC-CB). Methods: All consecutive patients between April 2013 to September 2017 undergoing CB ablation were included. Pulmonary vein angiograms were performed for anatomical delineation followed by PV freezing. Majority of patients received 6 hours post procedure recovery time which included a 4 hour femoral stop application as the standard practice of care. Results: 161 procedures were performed over four and half years. Same day (Day Case, DC) CB discharges included 40 cases (age: 58.7±10.7, F/M: 11/29) whilst overnight stays (Non-Day Case, NDC) consisted of 121 cases (age: 62.5±10.1, F/M:54/67). Similar calculated CHA2 DS2 VASc (DC-CB:1.825±1.48 vs NDC-CB:1.69±1.41, P =0.7) and HASBLED scores (DC-CB: 1.05±0.81 vs NDC-CB: 0.86±0.82, P =0.2) were noted. Both groups had similar number of persistent and paroxysmal AF, 20% and 80% respectively. Mean fluoroscopy time was 36±12 mins with a corresponding DAP of 24.5±19.8 Gy/cm 2 . Mean procedure time was 181±47 mins in NDC_CB and 152±37 mins in DC_CB ( P 0.001). Additional cavo-tricuspid isthmus dependent flutter ablation was performed in 21% NDC-CB and 15% DC-CB respectively. Over the five-year period, DC-CB ablation procedures increased rapidly whilst NDC-CB procedures reduced (figure 1). Procedure times in both groups improved with operator experience (table 1). A higher proportion of patients were on NOACS in the DC-CB group with an overall decline in warfarin use. Procedural complication rate was 1.8% [(n=3/161); phrenic nerve injury (n=2) and vascular injury requiring intervention (n=1)]. Readmission rates were none in DC-CB and 2 in NDC-CB (phrenic nerve injury n=2). The low composite complication rates suggest feasibility of the same day CB discharges. In this series, the overall 6 hour recovery period stipulated in the majority of cases (as part of the initial 2013/14 safety protocol) alongside procedures performed in the afternoon resulted in more overnight stays. Day case CB procedures facilitated an overall £12 000 savings over this analysis period (figure 2). Conclusion: Cryo-balloon (CB) ablation performed as day case (DC) procedures are safe and cost saving. As operator experience increases, shorter procedure duration, catheter dwell time and recovery periods alongside the financial savings would see the trend in DC-CB procedures superseding NDC-CB procedures with the emergence of Cryo-lounges in the near future.